Availability and quality of routine morbidity data: review of studies in South Africa. (29th June 2016) - Roomaney, Rifqah A; Pillay-van Wyk, Victoria; Awotiwon, Oluwatoyin F; Nicol, Edward; Joubert, Jané D; Bradshaw, Debbie; Hanmer, Lyn A
Abstract : Objectives: Routine health information systems (RHISs) provide data that are vital for planning and monitoring individual health. Data from RHISs could also be used for purposes for which they were not originally intended, provided that the data are of sufficient quality. For example, morbidity data could be used to inform burden of disease estimations, which serve as important evidence to prioritize interventions and promote health. The objective of this study was to identify and assess published quantitative assessments of data quality related to patient morbidity in RHISs in use in South Africa. Materials and Methods: We conducted a review of literature published between 1994 and 2014 that assessed the quality of data in RHISs in South Africa. World Health Organization (WHO) data quality components were used as the assessment criteria. Results Of 420 references identified, 11 studies met the inclusion criteria. The studies were limited to tuberculosis and HIV. No study reported more than 3 WHO data quality components or provided a quantitative assessment of quality that could be used for burden of disease estimation. Discussion: The included studies had limited geographical focus and evaluated different source data at different levels of the information system. All studies reported poor data quality. Conclusion: This review confirmed concerns about the quality of data in RHISs, and highlighted the need for a comprehensive evaluation of the quality of patient-level morbidity data in RHISs in South Africa.